The Impact of the Implementation of the Internal Quality Assurance System on Student Satisfaction in Academic Services - Koswara Deni; Dedy Achmad Kurniady; Aan Komariah; Enjang Yusup Ali (JTP - Jurnal Teknologi Pendidikan, 2026)
This study aims to examine the effect of the Internal Quality Assurance System implementation on student satisfaction with academic services in higher education. Using a quantitative explanatory design, data were collected from 200 active students selected through proportional random sampling. The research instrument consisted of a structured questionnaire measuring the implementation of the quality assurance cycle and student satisfaction across service quality dimensions. All items were declared valid and highly reliable, indicating strong internal consistency. The novelty of this study lies in its integration of the continuous quality assurance cycle with multidimensional measures of student satisfaction through a unified analytical framework, which goes beyond previous studies that typically examine these components in isolation. Specifically, this study provides empirical evidence by simultaneously analyzing multiple dimensions of student satisfaction within each stage of the quality assurance cycle, offering a more comprehensive and systematic understanding of their interrelationship.  Descriptive results show that the implementation of the internal quality assurance system is categorized as good, while student satisfaction with academic services is high. Inferential analysis reveals that the implementation of the Internal Quality Assurance System has a positive and statistically significant effect on student satisfaction (β = 0.812, p < 0.001), explaining a substantial proportion of variance (R² = 0.659). These findings confirm that systematic planning, implementation, evaluation, control, and continuous improvement of standards contribute to more structured, transparent, and responsive academic services. Therefore, higher education institutions should strengthen participatory and sustainable quality assurance practices as a strategic policy to enhance service quality, institutional competitiveness, and long-term student satisfaction.